Examination of Sustainability in Airport Terminal Buildings within the Framework of LEED Certificate - Celik, Figen; Gorgulu, S. Tulin (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2021)
Today, convenient and flexible transportation has greatly promoted the rapid development of the global economy and society, but at the same time, the increase in traffic has also negatively affected sustainability. While promoting economic development and solving social employment issues, aviation has also caused huge environmental impacts. For this reason, airports around the world, especially since the early 2000s, create a more environmentally friendly corporate profile with the pressure of various internal and external stakeholders, to reduce the environmental and socioeconomic impacts caused by aviation operations, and try to provide a safe and inspiring work environment for both users and employees. It is just one of these efforts that an increasing number of airport operating organizations are certified for widely used rating systems. Recently, an increasing number of airport authorities around the world have been receiving certificates of sustainable rating systems valid worldwide for their terminals and service buildings. These certification systems are issued to ensure sustainable building practice and to mitigate certain environmental impacts; while they encourage the use of the most effective techniques to reduce water and energy consumption, provide regulations on land use, pollutants and waste management, they actually fail to solve aviation-related problems. With the present study, it was aimed to examine the terminal buildings where the LEED green building certification system is applied, their competence in airport sustainability by making comparative analyzes to find the strengths and weaknesses of the certificate. LEED Certification System, the most widely used green building certification system in world, has selected as research subject and also it was aimed to investigate the contribution of the certificate to the sustainability of the airports. Terminals with LEED certification have been selected and analyzed comparatively because they are the first in their category. For this purpose, literature review method, one of the data collection methods, was used to collect information about the sustainable airport development process. In the literature review method, conferences, studies, academic publications, journals, books, rating systems that disclose airport sustainability performance, sustainability guidelines published by aviation authorities, practices deemed by the authorities and internet resources were examined. Considering the sustainable design approaches in the LEED green building rating system, certified airport terminal buildings examined within the scope of the study, and it is seen that similar design decisions are generally taken. As a result of the examination; it has been determined that studies on land selection, energy, indoor air quality and innovation gain importance, and terminals that score points in these titles receive positive opinions. LEED rating system focuses on the physical health of people in a wide range such as indoor air quality, acoustic and thermal comfort, lighting, and ventilation. In addition, the use of recycled and certified materials is encouraged, and the use of alternative water resources such as water conservation, quality, recycling and the use of gray water is supported. It must be kept in mind that the airport behaves as a set of very different spaces and each of these spaces should be evaluated seperately. The airport includes terminal buildings for commercial activities and passenger treatment (cafeterias, restaurants, shops, etc.). It also includes buildings and facilities where the air traffic is managed or basic aeronautical activities are carried out. These infrastructures will differ greatly from the existing certifying models for buildings. Airport operations involve a range of functions that affect the environment, including operation of aircraft; operation of airport and passenger vehicles and airport ground service equipment, de-icing and anti-icing of aircraft and airfields; fueling and fuel storage of aircraft and vehicles; airport facility operations and maintenance; and construction. As a result; it has been determined that a complex system such as airports is insufficient for LEED certification, and it has been proposed to establish an alternative rating system to cover the planning, design and construction and implementation stages of airports. For this purpose, it is necessary to develop a functional rating system model that facilitates the evaluation of the landside and airside facilities of the airport. In this way, studies for evaluating the facilities that interact with each other and reducing the environmental impacts caused by aviation can be carried out simultaneously. The rating system to be used to ensure and establish sustainability; must be directly proportional to the capacity, size and function of the airport and comply with local / regional legislation and regulations for airports. Because of the airports consist of landside and airside facilities and these facilities have their own problems the proposed system should be arranged to cover the planning, design and construction, operation and maintenance phases of the airports and should include arrangements for Land Side and Air Side facilities within itself.
Keywords: Airport passenger terminal; green airport; LEED certificate; sustainability; sustainable aviation; Architecture